Realizing Peace in the Digital World: Community Participation in Spreading Messages of Peace on Social Media - Zaky, Muhammad; Dilawati, Rika (Integritas Terbuka: Peace and Interfaith Studies, 2024)
The dissemination of messages of peace on social media has a significant impact on shaping public opinion and attitudes toward social and political issues. However, there is still limited understanding of how messages of peace are disseminated and received by social media users. This research aims to explore and understand how messages of peace are disseminated and understood by social media users, as well as the factors influencing this process. A qualitative approach is used in this research with data collection procedures through online observation and in-depth interviews with 30 social media users. Data were analyzed through data restatement, data display, and data verification steps. The findings of the research indicate that social media users have various ways of disseminating messages of peace, ranging from sharing positive content to debating controversial issues with a peaceful approach. Factors such as content, social context, and user identity influence the effectiveness of messages of peace in achieving their dissemination goals. This research concludes that the dissemination of messages of peace on social media is a complex phenomenon influenced by various factors. However, with a deeper understanding of patterns and factors influencing the dissemination of messages of peace, more effective strategies can be developed to promote peace and tolerance in the online world.